Analysis Off @Wardahbeauty_Bengkulu's Instagram Marketing Communication Strategy In Maintaining The Brand - Bela, Melisa Prana; Sari , Sapta; Yanto, Yanto (Social Sciences Journal, 2025)
The development of social media, especially Instagram, has become a significant opportunity for the beauty industry in building brand awareness and relationships with consumers. Wardah Beauty Bengkulu utilizes the @wardahbeauty_bengkulu account as its primary medium to maintain its image as a halal cosmetic brand amidst increasing market competition. This study aims to analyze the digital marketing communication strategies implemented by the account to maintain its brand in the Bengkulu region. The research method used a descriptive qualitative approach, with data collection techniques including observation of Instagram content, documentation, and in-depth interviews with account administrators, beauty advisors, and active consumers. The analysis was conducted using the AIDA (Attention, Interest, Desire, Action) theory and the Brand Equity concept. The results show that Wardah implements a communication strategy that includes visual consistency in line with its halal identity, educational content, collaboration with local influencers, and integration of online and offline activities through events such as beauty classes and skin checks. This strategy effectively attracts attention, builds interest, increases desire through testimonials and direct experiences, and encourages purchasing actions. In conclusion, the digital communication strategy through Instagram has proven to be able to strengthen brand awareness, maintain the image of modern halal cosmetics, and increase consumer loyalty in Bengkulu.